2014
DOI: 10.1016/j.ijvsm.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genotyping of the infectious bursal disease virus (IBDV) isolated from Broiler Flocks in Egypt

Abstract: Re-emergence of highly virulent forms of IBDV has been the cause of significant economic losses. In present study, 52 bursa samples were assayed using reverse transcriptase-polymerase chain reaction (RT-PCR) for IBDV targeting VP2 gene. Out of the tested samples 20 were positives. Eleven IBDV-positive samples were selected for further isolation and characterization. Histopathological analysis of the bursa revealed necrosis, presence of depleted follicles and some infiltration of heterophils, characteristic to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 25 publications
14
35
0
1
Order By: Relevance
“…Very virulent IBD viruses (vvIBDVs) have been isolated in Asia, Central Europe, Russia, the Middle East, and South America (van den Berg, 2000). In Egypt, both vvIBDV strains and variant IBDV strains were reported and has been a serious problem circulating in flocks vaccinated using classical IBDV vaccines (Metwally et al 2009, Helal et al, 2012, Mohamed et al, 2014and Sara et al, 2014. Diagnosis of IBDV depends on isolation of the suspected virus then serological identification using FAT, ELISA, and AGPT but detection of IBDV using RT-PCR showed superior results and greater sensitivity and specificity than the serological techniques (van den Berg, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Very virulent IBD viruses (vvIBDVs) have been isolated in Asia, Central Europe, Russia, the Middle East, and South America (van den Berg, 2000). In Egypt, both vvIBDV strains and variant IBDV strains were reported and has been a serious problem circulating in flocks vaccinated using classical IBDV vaccines (Metwally et al 2009, Helal et al, 2012, Mohamed et al, 2014and Sara et al, 2014. Diagnosis of IBDV depends on isolation of the suspected virus then serological identification using FAT, ELISA, and AGPT but detection of IBDV using RT-PCR showed superior results and greater sensitivity and specificity than the serological techniques (van den Berg, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…All the Senegalese IBDV strains had the same amino acid sequences at positions 253 (Q), 279 (D) and 284 (A). Similarly, Mawgod et al (2014) reported the same amino acid sequences at these positions of the VP2 in field strains in Egypt. The amino acids at positions 253 and 284 were found to be responsible for pathogenicity and are unique to highly virulent IBDVs (Brandt et al, 2001).…”
Section: Discussionmentioning
confidence: 62%
“…Subsequently, IBD has become a major player among infectious diseases of broilers and pullets, despite routine implementation of vaccination. For improved control of this disease in Senegal, genetic evolution of fifteen Senegalese IBDV strains isolated in 1979, 1999, 2012and 2014 was studied. The hypervariable region of the VP2 gene of these field strains was sequenced and compared to each other and to published sequences obtained from GenBank.…”
Section: Introductionmentioning
confidence: 99%
“…To determine antigenic difference among vaccine and field strains, the deduced amino acid substitutions in the variable VP2 (vVP2) region (206-350 aa) [12] were analyzed ( Fig. 3).…”
Section: Resultsmentioning
confidence: 99%